Use of Acrobatic Exercises in Readiness Formation of Young Handball Players for Competitions - Yuri Tsyupak; Alexander Shvay; Leonid Hnitetskyy; Andrei Kovalchuk (Lesya Ukrainka Volyn National University, 2017)
The article deals with the feasibility and effectiveness of acrobatic exercises in training sessions for young handballers in preparations. In terms of increasing the density of the game, increasing the combat power on the ground, implementation of complex technical elements in modern handball topical issues including the structure of the training process of exercise that will help speed development, coordination, and promote the education of children volitional qualities. The offered method of the use of acrobatic exercises is in trainings employments. For verification of efficiency of application of acrobatic exercises and with the purpose of determination of changes in the indexes of physical and technical preparedness the young handballers of investigational groups had the conducted testing. A pedagogical experiment confirmed efficiency of application of method of the use of acrobatic exercises in trainings employments of young handballers.